Ensuring Intention to Manage Sports Events through Positive Work Climate and Motivation: An Empirical Study on Sports Volunteers of China - Qian Sha (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The concept of volunteerism revolves around the voluntary participation or involvement of a person in any agency, community or organization. The purpose of such involvement is to generate benefits not only at a personal level but for the organization or community where their person volunteers. A trend has been observed that the demand of volunteers has increased dramatically in different sectors but the number of potential volunteers are decreasing dramatically. Moreover, it has become quite a challenge for organizations to retain their volunteers. In this regard, the current study was aimed at finding out how the factors of work climate and intrinsic motivation influence the continuance intention of the sports volunteers in China in the presence of three mediating variables, attitude, emotional exhaustion and volunteer satisfaction. The quantitative data has been gathered from 344 sports volunteers from China through survey questionnaires and has been analyzed statistically. The results of analysis have indicated that the impact of work climate on continuance intention is significant and positive. However, the impact of intrinsic motivation on continuance intention is found to be insignificant. In case of mediating impact, the results indicate that attitude and volunteer satisfaction have significant mediating impact on the relationship of both intrinsic motivation and work climate with continuance intention. However, the mediating impact of emotional exhaustion is significant only in case of work climate and insignificant in case of intrinsic motivation.